Influence of culture on dietary practices of children under five years among Maasai pastoralists in Kajiado, Kenya. Issue 1 (December 2015) - Chege, Peter; Kimiywe, Judith; Ndungu, Zipporah
Abstract Background and objectives Globally, children aged under five years are prone to malnutrition. Maasai are a nomadic community in Kenya still upholding traditional and has a high rate of child undernutrition. Consideration of cultural practices is a pre-condition for ensuring appropriate dietary practices. However, information on the influence of culture on dietary practices among Maasai children is minimal. The possible influence of culture on dietary practices among these children was investigated. Methods Six focus group discussions sessions each consisting of 10 mothers were conducted from two randomly selected villages in Sajiloni location, Kajiado County. Results Results from this study showed that children mainly consume cereals and legumes. Nomadism makes animal products inaccessible to most children. Livestock are considered a sign of wealth, thus mainly slaughtered on special occasions. Additionally, selling of animals or animal products is not encouraged limiting income that would improve the food basket. Some food taboos prohibit consumption of wild animals, chicken and fish limits the household food diversity. Consumption of vegetables is limited since they are perceived to be livestock feed. The belief that land is only for grazing contributes to low crop production and consumption thus the diets lack diversification. Maasai culture encourages introduction of blood, animal's milk and bitter herbs to infants below six months, which affects exclusive breast feeding. The men are prioritized in food serving leading to less and poor quality food to children. The consumption of raw meat, milk and blood is likely to lead to infections. The practice of milk fermentation improves bioavailability of micronutrients and food safety. Socialism ensures sharing of available food while believe in traditional medicine hinder visit to health facilities thus no access to nutrition education. Conclusion This study concludes that culture influence the dietary practices among children under five years. It recommended initiation of programs to create awareness on how the beliefs negatively affect dietary practices with a view for a change.